(3GdJJeI aj bQGAI GdKdGKI GdCFeIs - (3UObI Hf SdGeI Hf MSjf, TQa GdOjf GdnerSnMnQGpFj,J (B825 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3CeG HYO aEfg deG enf Gddg Ydni HMaX cJGHg GdYRjR henf Ydj MJi bQCJg HGdbQGAGJ GdYTQI hQMdJ aj WdH s
(3BNQgG (B:s
(3bQC GdKdGKI dgH HaJM GdgGA hdjS NdGa GdKdGKI ef GdeSJfjQ hGdEQTGO aj ShQI GdENdGU hGdadb hGdfGS Je GdNdGa aj GdCUhd hddg GdMeO hGdefg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B75 - (3U(B167s
(3Cced Hg cJGH GdEQTGO hcPdc cJGH GdeSJfjQddTjN TeS GdOjf CHhGdaJM eMeO GdYSbdGfis
(3GdfSNI HgG MhGTs
(3HBNQgG ahGFOs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs